ANALISIS TAYANGAN FILM UPIN-IPIN DI MNCTV DALAM MERUBAH PERILAKU ANAK SEKOLAH DASAR NEGERI 07 BERMANI ILIR - M. Fadel Satria (UNIVED PRESS, Universitas Dehasen Bengkulu, 2020)
The development of technology that continues to evolve to encourage creativity to continue to be present until the presence of cartoon films that air in mass media such as television. Cartoons like Upin-Ipin are shown on television with the aim of a children's audience. The storyline and scenes in the Upin-Ipin cartoon movie need to be a concern because children easily understand what they see and hear so that they do not close off watching children who need help changing policies. This study uses descriptive qualitative research that addresses the phenomena discussed in the field. Data collection techniques by interview, observation and documentation. In analyzing data, researchers use theories that uses and gratification whereby media consumers have the freedom to decide how (through which media) they use the media and how the media will impact on him.The results of a study stating the desire of SDN 07 Bermani Ilir grade 2 children to watch upin and ipin shows were highly welcomed, they were also very fond and happy to meet their needs after watching Upin-Ipin films on MNCTV Malaysia) funny stories and familiar backgrounds with the audience of children, from their hobbies and needs being met the children determine their own effects from watching the cartoon movie by imitating the language style Upin-Ipin and other characters in the cartoon also the students apply it in everyday life including in school environment.